2020
DOI: 10.1039/c9fo02296a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the anti-inflammatory properties of grape pomace treated by Trametes versicolor

Abstract: The application of solid-state fermentation for the production of value-added products from the agro- and food-industry residues has been recently investigated greatly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Phenolic compounds are one of the largest groups of natural compounds and possess a wide range of biological activities (antioxidative, anti-inflammatory, anti-allergenic, antiviral, anticancer, antimicrobial, antimutagenic and cardioprotective, etc.) related to their structural diversity [ 1 ]. In the last 30 years, research has been mainly focused on: (a) determination of the phenolic compounds profile from various plant materials [ 2 , 3 ]; (b) determination of biological activity, especially antioxidant activity [ 4 ] and more recently antitumor activity [ 5 ]; (c) development and optimization of different extraction methods for phenolic compounds [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are one of the largest groups of natural compounds and possess a wide range of biological activities (antioxidative, anti-inflammatory, anti-allergenic, antiviral, anticancer, antimicrobial, antimutagenic and cardioprotective, etc.) related to their structural diversity [ 1 ]. In the last 30 years, research has been mainly focused on: (a) determination of the phenolic compounds profile from various plant materials [ 2 , 3 ]; (b) determination of biological activity, especially antioxidant activity [ 4 ] and more recently antitumor activity [ 5 ]; (c) development and optimization of different extraction methods for phenolic compounds [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another related study with pomace supports this consideration and the necessity to define the optimum fermentation period. The high polyphenol and bioactivity in the beginning of the fermentation period were followed by the reduction in both indicators (polyphenol content and biological activity) as fermentation progressed up to 15 days [74]. Additionally, Teles et al [53] reported increasing polyphenol content and antioxidant activity during the fermentation of grape pomace with Aspergillus niger during a shorter period (96 h) in relation to these aforementioned studies.…”
Section: Release and Production Of Bioactive Compoundsmentioning
confidence: 77%
“…When grape pomace was treated with Trametes versicolor TV-6 the concentration of phenolic acids, flavan-3-ols and rutin increased while the concentration of anthocyanins decreased. Those changes resulted in enhanced anti-inflammatory activity of obtained extracts which was measured by the inhibition of 5-lipoxygenase and hyaluronidase [20]. Also polyphenols produced by Xylaria nigripes demonstrated enhanced anti-inflammatory properties which were verified by the inhibition of cyclooxygenase-2 [24].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 94%
“…In the majority of cited papers anti-inflammatory properties of extracts containing polyphenols were not verified despite the fact that there were some compounds among them which demonstrate such activity [76,77]. Research mainly focused on antioxidant properties [20,22,23,31]. This applies to various studies involving organisms providing increase of particular phenolic compounds: Rhizopus oligosporus NRRL 2710 -rutin [22], Prunus armeniaca L -cinnamic acids and selected flavonols [31]; Lactobacillus plantarum CECT 748 -hydroxybenzoic acids and flavonols [78]; Eurotium cristatum YL-1 -isoflavones (daidzin, daidzein, genistin and genistein) [34]; Rhizopus oryzae and Aspergillus foetidus -tannins [35]; Rhizopus oryzae RCK2012 -phenolic acids [36]; Aspergillus oryzae LBA01 -3,4-di-hydroxybenzoic acid, ferulic acid, vanillic acid and quercetin [37].…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation